Energy Efficiency in the Minerals Industry Best Practices and Research Directions (Green Energy and Technology,, 2018)
This book presents a state-of-the-art analysis of energy efficiency as applied to mining processes. From ground fragmentation to mineral processing and extractive metallurgy, experts discuss the current state of knowledge and the nagging questions that call for further research. It offers an excellent resource for all mine managers and engineers who want to improve energy efficiency to boost both production efficiency and sustainability. It will also benefit graduate students and experienced researchers looking for a comprehensive review of the current state of knowledge concerning energy efficiency in the minerals industry.